IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER (PUG) BIDANG PENDIDIKAN DI STUDI KASUS SMP NEGERI 37 KOTA MEDAN - Harefa, Novitasari; Pasaribu, Vera A.R.; Rajagukguk, Jonson (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This paper attempts to answer the question of what programs have been implemented by the Medan City Education and Culture Office in implementing the PUG policy in the field of education and what are the supporting and inhibiting factors in implementing the PUG policy in the field of education at the Medan City Education and Culture Office and SMP Negeri 37 Medan City. The research method used in this study is a descriptive research method with a qualitative approach. The informants in this study were the Head of Institutional Facilities and Infrastructure of Junior High Schools at the Medan City Education and Culture Office and the Principal of SMP Negeri 37 Medan City. Data collection was carried out using documentation and interview techniques. The data analysis technique used the John W. Creswell analysis technique, (2015). The results of this study indicate that institutionally the implementation of the PUG policy in the field of education has been implemented through programs run by the Medan City Education and Culture Office. However, the facilities and infrastructure that have not been 100% fulfilled and the lack of parental support for the programs implemented in schools, have caused the implementation of the PUG policy in the field of education at SMP Negeri 37 Medan City to still not be implemented optimally